2011
DOI: 10.1088/1674-4926/32/10/104003
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the failure mechanisms of microwave bipolar transistors caused by electrostatic discharge

Abstract: Electrostatic discharge (ESD) phenomena involve both electrical and thermal effects, and a direct electrostatic discharge to an electronic device is one of the most severe threats to component reliability. Therefore, the electrical and thermal stability of multifinger microwave bipolar transistors (BJTs) under ESD conditions has been investigated theoretically and experimentally. 100 samples have been tested for multiple pulses until a failure occurred. Meanwhile, the distributions of electric field, current d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Experiment results showed that the bipolar devices in the LNA are most vulnerable to the damage by the external electrical stress. [2] In the past few years, a significant number of studies have been carried out to investigate the damage induced by the EMI on the bipolar devices, [3][4][5][6][7][8][9][10][11][12] which provides a certain theoretical basis for the electromagnetic assessment and hardening design.…”
Section: Introductionmentioning
confidence: 99%
“…Experiment results showed that the bipolar devices in the LNA are most vulnerable to the damage by the external electrical stress. [2] In the past few years, a significant number of studies have been carried out to investigate the damage induced by the EMI on the bipolar devices, [3][4][5][6][7][8][9][10][11][12] which provides a certain theoretical basis for the electromagnetic assessment and hardening design.…”
Section: Introductionmentioning
confidence: 99%